Development and characteristics of a tourist visit in Slovenia from 1950 - Horvat, Uroš (Journal for Geography, 2018)
The author points out the main periods of tourist development in Slovenia after 1950, using the data of a tourist visit (the number of tourists and overnight stays, the average length of stay of tourists, their nationality, the seasonality of the tourist visit, the distribution by type of accommodation and type of tourist resort). He emphasizes the importance of building of tourist infrastructure and accommodation capacities, changes of the tourist flows, the impact of political events and other factors that influenced on the development of tourism in Slovenia.